Pengaruh Variasi Pemberian Dosis POC Kulit Pisang terhadap Pertumbuhan Daun Stek Peppermint (Mentha piperita L.) - Rizkika Maulida; Ervina Titi Jayanti; Firman Ali Rahman (Agroinovasi: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Variations in the provision of fertilizers to plants have an important role and support the growth and development of plants, one of which is the peppermint plant (Mentha piperita L.). This study aims to determine the effect of giving variations in the dosage of liquid organic fertilizer of banana peels on the productivity of leaf growth of peppermint plant cuttings (Mentha piperita L.). Analysis of plant growth data using statistics with factorial Anova test and with 5% BNT test if the data is significant. The results showed that giving variations in the dosage of liquid organic fertilizer of banana peels had a significant effect on the growth of leaves of peppermint plant cuttings (Mentha piperita L.). The dosage of 100 ml of uli banana peel POC (P3U1) gave the best results on branch growth and dry leaf weight, while the dosage of 87.5 ml of uli banana peel POC (P2U1) was optimal for the growth of the number of leaves, and the dosage of 100 ml of kepok banana peel POC (P3U2) produced the highest fresh leaf weight.